Humans, Elves, and Greenland Sharks: Against Kagan’s Distributive Argument for Hierarchical Moral Status - Crummett, Dustin R (DigitalCommons@CalPoly, 2020)
Shelly Kagan argues that “unitarianism,” the claim that animals and humans have equal moral status, has intuitively implausible distributive implications. I argue that Kagan’s reasoning can, with certain modifications, be applied equally well to undermine his own view, and that the responses Kagan can make to this modified reasoning are also available to the unitarian responding to Kagan’s original argument. Accordingly, Kagan cannot consistently hold his own view while also endorsing his main against unitarianism.